Janji Berkat Ismael: Kontra Argumen Terhadap Islamofobia dan Implikasi Bagi Misi Gereja - Shekinah Theofany; Normando Justine (Sekolah Tinggi Teologi Kharisma, 2023)
AbstractIslamophobia is an attitude that is widespread, especially among Christians. This attitude is one of the obstacles to evangelism and the mission of the church. Using a qualitative descriptive and literary study method, this research aims to make the church aware of the importance of Ishmaelites and Muslims as targets of God's mission of love to fight Islamophobia. The results of the discussion put forward Islamophobia in a Christian environment, the relationship between Ishmael and Islam, the meaning and content of Ishmael's Blessing Promise, and its implications for the church and mission. The conclusion from this discussion is that Islam has a correlation with Ismail and Christians have a duty as a means of mission, namely to preach the Gospel and show love for Muslims. AbstrakSikap Islamofobia merupakan sikap yang marak terutama di kalangan Kristen. Sikap ini merupakan salah satu hambatan penginjilan dan misi gereja. Dengan metode Deskriptif Kualitatif dan Studi Pustaka, penelitian ini bertujuan supaya gereja menyadari pentingnya keturunan Ismael dan umat Islam sebagai sasaran misi kasih Allah guna melawan sikap islamofobia. Hasil pembahasan mengemukakan islamofobia dalam lingkungan Kristen, hubungan antara Ismael dan Islam, Makna dan isi Janji Berkat Ismael, serta implikasinya terhadap gereja dan misi. Kesimpulan dari pembahasan ini adalah bahwa Islam memiliki korelasi dengan Ismail dan umat Kristen memiliki tugas sebagai sarana misi ialah untuk mengabarkan Injil dan menunjukkan kasih terhadap umat Islam.